2014
DOI: 10.1590/1678-457x.6415
|View full text |Cite
|
Sign up to set email alerts
|

Peptide separation of commercial fermented milk during refrigerated storage

Abstract: Milk is an important source of bioactive compounds. Many of these compounds are released during fermentation and refrigerated storage. The aim of this study was to determine the release of peptides by lactic acid bacteria in commercial fermented milk during refrigerated storage. The size and profile of peptides were analyzed by polyacrylamide gel electrophoresis and sizeexclusion HPLC. During electrophoresis, it was observed that the peptides were released from caseins, whereas β-lactoglobulin was the whey pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…In this respect, it is known that phenolic or polyphenol has an aromatic ring one or more phenol hydroxyl substituents (Lattanzio et al, 2006). The existing of aromatic amino acids in the peptide fractions caused by proteinase and peptidase activity in the proteolytic system of lactic acid bacteria are released and accumulated during cold storage (González-Olivares et al, 2014). Metabolites of aromatic amino acids such as phenylalanine and tryptophan were phenolic and indolic compounds (Dai et al, 2011).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In this respect, it is known that phenolic or polyphenol has an aromatic ring one or more phenol hydroxyl substituents (Lattanzio et al, 2006). The existing of aromatic amino acids in the peptide fractions caused by proteinase and peptidase activity in the proteolytic system of lactic acid bacteria are released and accumulated during cold storage (González-Olivares et al, 2014). Metabolites of aromatic amino acids such as phenylalanine and tryptophan were phenolic and indolic compounds (Dai et al, 2011).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…After separation of hydrolyzates into fractions using either a one‐dimensional or multidimensional system, electrophoretic and/or mass spectrometric analyses can be used in combination to enhance the identification of peptides. Besides, electrophoresis can also be utilized as a tool for peptide separation based on the isoelectric point and molecular mass distribution in gel wells (González‐Olivares, Añorve‐Morga, Castañeda‐Ovando, Contreras‐López, & Jaimez‐Ordaz, ; Koval et al, ; Naimah, Al‐Manhel, & Al‐Shawi, ). The isoelectric focusing point relies on the pH gradient ranging from 3 to 10 under the influence of an electric field, whereas the molecular mass distribution is based on the electrophoretic mobility of the molecule.…”
Section: Structure‐informed Separation Processesmentioning
confidence: 99%
“…2). This is related to the fact, that lactic acid bacteria fulfil their nitrogen requirements mainly through caseins hydrolysis, for example in commercial fermented milks casein concentration is reduced around 50% 36 . In the current study, no sufficient changes in the hydrolysis of casein and a wrong separation were observed in the fermentation with L. casei Shirota at time 2 (according the bands separated); for this reason this result is only presented in Figure 1.…”
Section: Peptides Separation By Tris-tricine Sds-pagementioning
confidence: 99%